Medial Shoulder Instability: Prevalence and Treatment Outcomes in 17 Poodles and 31 Dogs of Other Breeds - Woolley, E.L.E.; Collyer, T.A.; Finch, S.J.; House, A.K. (VCOT Open, 2023)
Objective The aim of this retrospective multicenter study was to investigate whether poodles were overrepresented in a cohort of dogs with medial shoulder instability (MSI), and to compare the incidence of spontaneous (nontraumatic) MSI and treatment outcome in poodles and non-poodle dogs.Study Design Medical records (2009–2019) of dogs with MSI from five surgical referral centers were reviewed.Results Forty-eight dogs with confirmed MSI were enrolled; 17 (35%) of which were poodles and 31 (65%) were of other breeds (including 11 [23%] poodle crossbreeds). Poodles were more than 10 times overrepresented in the MSI populations (p < 0.0001) compared with other breeds. MSI occurred spontaneously in 82% of poodles and 52% of non-poodles; the odds of presenting with spontaneous MSI for poodles were four times greater than that for non-poodle breeds. There were no differences in terms of treatments and outcomes.Conclusion Poodles were significantly overrepresented in the cohort of dogs presenting with MSI and were more likely to have spontaneous rather than traumatic MSI.
Keywords: dogs; medial shoulder instability; poodle